TIME AND COST ACCELERATION ANALYSIS USING CRASHING METHOD (CASE STUDY: TANJUNG UNCANG JETTY CONSTRUCTION PROJECT BATAM CITY) - Putra, Harisa Ramadhani; Koespiadi, Koespiadi; Oetomo, Wateno (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
Contractors involved in construction projects face the crucial challenge of effectively managing time to ensure the timely completion of the project as stipulated in the contract, if not earlier. Efficient time management not only facilitates adherence to contractual obligations but also transforms incurred costs into profitable outcomes, thereby preventing financial penalties associated with project delays. Consequently, the strategic implementation of acceleration efforts emerges as a pivotal solution to address and mitigate the complexities inherent in construction project timelines. The acceleration process is intricately tied to the identification and prioritization of critical activities within the project schedule. By employing a comprehensive approach that integrates both cost and time analyses, the Crashing method with additional modifications emerges as a valuable tool in this endeavor. The Crashing method involves a strategic acceleration of critical activities, coupled with a meticulous calculation of the additional costs incurred due to the acceleration process. A compelling case study that exemplifies the efficacy of the Crashing method and its supplementary measure of alternative overtime work is evident in the Tanjung Uncang Pier construction project in Batam City. Through the meticulous application of the Crashing method and the incorporation of alternative overtime work, the project's completion timeline was successfully curtailed from the originally delayed schedule of 257 calendar days to a more expedited 244 calendar days.